The Development and Standardization of a Proctological Agent Based on Black Cumin (Nigella Sativa L.) Extract (Indian Journal of Forensic Medicine & Toxicology, 2022)
Annotation. Nigella sativa L. (Ranunculaceae) is one of the promising plants that has a wide spectrum of pharmacological activity. The black cumin is known to have been used for the treatment of cataracts, bronchial asthma, cholelithiasis and urolithiasis, helminthic invasions, diabetes, hemorrhoids, and many other diseases.The aim of this study is to develop and standardize a drug based on a dry extract of the black seed– black cumin (Nigella sativa L.).The technology of preparing suppositories of N. sativa dry extract by fusion molding was proposed, and its antiulcer activity was studied. The quality of suppositories was assessed according to the following indicators: characteristics, average weight of suppositories, melting point, identification, quantification. The study of the antiulcer activity of the drug was carried out on the model of phenolic proctitis. It was found that the tested drug significantly reduces the area of necrosis, hyperemia, and also significantly reduces the edema and the length of the damaged section of the intestine relative to the entire length of the rectum, on the model of phenolic proctitis. The data obtained indicate the presence of reliable antiulcer activity in the tested drug, which gives reason to recommend it for proctitis, hemorrhoids and in a number of other proctological diseases with concomitant inflammation, edema, hyperemia and ulceration.
Keywords: : dry extract of Nigella sativa, suppositories, thymoquinone, anti-inflammatory activity